Continuous Long-Term Anaerobic Co-digestion of Crude Glycerol and Domestic Sewage: Plug-Flow In-Series Reactor Performance and Microbiota Acclimatization - Adames, Luan Vieira [UNESP]; Pires, Lorena Oliveira [UNESP]; Maintinguer, Sandra Imaculada [UNESP] (Springer, 2022)
Long-term operation of four in-series horizontal anaerobic reactors with fixed bed (HARFB) R1, R2, R3, and R4 was conducted to evaluate the co-digestion of domestic sewage (DS) with different proportions of crude glycerol (CG) from biodiesel production. The main objective was to examine the effect of the increase of CG in the influent with the proportions of 1.5%, 2%, and 3% (v/v). The anaerobic co-digestion was conducted in sequential reactors with increasing diameters to favor the fermentation in the R1 and R2 and the methanogenesis in the R3 and R4. The increase in CG proportions in the influent resulted in mean OLRs of 18.06, 26.75, and 37.85 kg COD/(m(3) day) for 1.5%, 2%, and 3% of CG, respectively. The highest hydrogen production was (L H-2/(m(3) day)) 277.88 (R1, at the 1.5% CG) and 84.43 (R2, at the 2% CG). The highest methane volumetric production occurred during the 1.5% CG in R3 (306.7 L CH4/(m(3) day)), with a 98% COD removal. The configuration of four in-series reactors could promote total removals of CG, even at the 3% CG. Reactor R1 produced 4 g/L of 1,3-propanediol and 2.8 g/L of propionic acid. The changes in the microbiota were verified, mainly on how the Lactobacillales and Selenomonadales orders were favored, respectively, in the fermentative reactor (R1) and the methanogenic reactor (R3). The inhibition of the methanogens verified in the in-series reactors selected the Methanosarcinales order. Even though CG increased caused some instabilities in the reactor parameters, no toxic effect was reached and the HARFB in-series system showed robustness to removing CG continuously for extended times.
Keywords: Biogas; Hydrogen; Methane; Biodiesel; Anaerobic reactor; 1,3-Propanediol